The Role of Ludruk in Developing Communication, Self-Expression, and Social Skills in Elementary School - Windarti, Wiwik; Gunansyah, Ganes; Puspita, Ari Metalin Ika (IKIP PGRI Bojonegoro, 2025)
This study explores the role of Ludruk, a traditional Javanese performing art, in fostering communication skills, self-expression, and social development among elementary school children at SDN Gunungsari. Using a qualitative research design with a descriptive and analytical approach, the study investigates how Ludruk education influences children's interpersonal interactions and emotional expression. The research involved a purposive sample of teachers, students, and relevant stakeholders, and data were collected through interviews, observations, and literature studies. The findings indicate that Ludruk not only enhances students’ verbal and non-verbal communication but also encourages self-confidence and collaboration, which are crucial for social integration. The study highlights the importance of incorporating cultural arts like Ludruk in elementary education, demonstrating its potential to develop students' communication and social skills in meaningful and engaging ways. The research underscores the relevance of traditional arts in modern education and their role in holistic child development.